Volvulus complicating pregnancy. (16th November 2010) - Mechery, J; Wake, C
Abstract : A 29-year-old, primiparous woman, 35 weeks and 4 days of gestation presented with sudden onset of acute upper abdominal pain. She did not complain of decreased fetal movements or vaginal bleeding. She was treated with analgesics but had no relief despite strong analgesia. Later in the day fetal heart beats could not be identified. Her abdomen was tense and tender and a presumptive diagnosis of concealed abruption was made. Ultrasound scan confirmed intrauterine death with retroplacental clots. Labour was induced and she had a vaginal breech delivery. She continued to have constant upper abdominal pain with sharp exacerbations. On examination her abdomen was tender with guarding, rigidity and rebound tenderness. CT scan showed significant small bowel obstruction likely due to internal herniation and twisting in the left upper quadrant. Laparotomy revealed volvulus of the jejunum. She underwent small bowel resection and anastomosis and made an uneventful postoperative recovery. This case demonstrates, although uncommon volvulus can have potentially devastating consequences. Pregnancy masks the signs and symptoms of intestinal obstruction and therefore a high index of suspicion is required for a timely intervention and to minimise maternal morbidity, perinatal mortality and morbidity.